Efeitos do extrato de membrana amniótica comercial no temp de epitelização e na concentração da MMP-9 lacrimal em gatos com úlcera de córnea induzida experimentalmente - Silveira, Bruna Carvalho (2021)
The purpose of the study was investigated whether a commercially available AME can accelerate corneal wound healing and to suppress the early expression of MMP-9 in the tears of cats with experimentally induced superficial ulcerative keratitis. At the end of keratectomy, cats in the treatment group (TG, n = 8) received 40 μL of AME (EyeQ ® Amniotic Eye Drops, Vetrix ®) four times daily, while cats in the control group (CG, n = 8) received 40 μL of saline at the same time points. Tears were collected 24 and 48h after keratectomy, and the total MMP-9 was quantified by ELISA. The corneal re-epithelialization rate did not differ between groups (P = 0.26) being 0.48 ± 0.05 mm 2/h in the CG and 0.41 ± 0.03 mm 2 /h in the TG. Similarly, the average time to achieve corneal wound healing did not differ between groups (P = 0.25) and was 61.50±3.54 h in the CG and 70.50 ± 6.71 h in the TG. The dimensions of the ulcerated areas also did not differ at any time point between the groups (P > 0.05). In both groups corneas healed without scarring, pigmentation, or vascularization. The expression of MMP-9 in the tears was similar in both groups at 24h post keratectomy, with a slight decrease at 48 h (P > 0.05). The present study indicated that the instillation of a commercial AME (EyeQ ®) is safe, but it did not decrease the corneal re-epithelialization time and the early expression of MMP-9 in the tears of cats with experimentally induced superficial ulcerative keratitis. Hence, our results warrant further investigation of EyeQ ® in a clinical setting with cats presenting different types of naturally occurring corneal ulcers.